19y+60=-6

Simple and best practice solution for 19y+60=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19y+60=-6 equation:


Simplifying
19y + 60 = -6

Reorder the terms:
60 + 19y = -6

Solving
60 + 19y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + 19y = -6 + -60

Combine like terms: 60 + -60 = 0
0 + 19y = -6 + -60
19y = -6 + -60

Combine like terms: -6 + -60 = -66
19y = -66

Divide each side by '19'.
y = -3.473684211

Simplifying
y = -3.473684211

See similar equations:

| 3-6x-16-20x=7-9x | | 2(2-x)=9x-84 | | 22-4(-13)=12(-13)+126 | | M+6=-2m+6 | | (7x+4)-(24x-15)=180 | | 0.2(z+15)=3 | | 0.4x-1.2=0.15x+1.8 | | n(n-1)(n-2)(n-3)-84=0 | | y^4+26y^3+169y^2-900=0 | | h=-5 | | 15+8x=45+6x | | 11-6n=29 | | (3k+5)(-k)= | | 3(4x-4)+52=6x+4 | | 5x+1=6x+17 | | 3x+52=80 | | 2015=101b+19a | | 3c-7=-3+1 | | 47=47-8(5-1w) | | 2y=3y+19 | | 4x-2=2x+x+4 | | 1v+1=1v-6 | | 4(8+m)= | | -8+x+6=2x+x | | A(w-3)+5=3(w-1) | | 6r-1+6=6r | | 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 |

Equations solver categories